A new approach to variable selection in least squares problems - Osborne, MR; Presnell, B; Turlach, BA (IMA journal of numerical analysis, 2000)
The title Lasso has been suggested by Tibshirani (1996) as a colourful name for a technique of variable selection which requires the minimization of a sum of squares subject to an l1 bound κ on the solution. This forces zero components in the minimizing solution for small values of κ. Thus this bound can function as a selection parameter. This paper makes two contributions to computational problems associated with implementing the Lasso: (1) a compact descent method for solving the constrained problem for a particular value of κ is formulated, and (2) a homotopy method, in which the constraint bound κ becomes the homotopy parameter, is developed to completely describe the possible selection regimes. Both algorithms have a finite termination property. It is suggested that modified Gram-Schmidt orthogonalization applied to an augmented design matrix provides an effective basis for implementing the algorithms.